2011
DOI: 10.1007/s10546-011-9628-y
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Transport over Forested Hills

Abstract: Numerical simulations of scalar transport in neutral flow over forested ridges are performed using both a one-and-a-half order mixing length closure scheme and a large-eddy simulation (LES). Such scalar transport (particularly of CO 2 ) has been a significant motivation for dynamical studies of forest canopy -atmosphere interactions. Results from the one-and-a-half order mixing length simulations show that hills where there is significant mean flow into and out of the canopy are more efficient at transporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 26 publications
5
29
0
Order By: Relevance
“…Chen et al [60] Pollutant dispersion in the built environment Exp/Num − Sc t = 1.0 and corrected from wind tunnel data Hassan et al [65] Supersonic crossflow Exp/Num − Sc t = 1.0 and adaptive Sc t Galeazzo et al [64] Jet in crossflow Exp/Num − Sc t = 0.3-0.9 Goldberg et al [70] Different type of air flows Exp/Num − Sc t variable Ross [71] Flow over forested hills Exp/Num − Sc t = Sc t (z)…”
Section: Environmental Flow Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al [60] Pollutant dispersion in the built environment Exp/Num − Sc t = 1.0 and corrected from wind tunnel data Hassan et al [65] Supersonic crossflow Exp/Num − Sc t = 1.0 and adaptive Sc t Galeazzo et al [64] Jet in crossflow Exp/Num − Sc t = 0.3-0.9 Goldberg et al [70] Different type of air flows Exp/Num − Sc t variable Ross [71] Flow over forested hills Exp/Num − Sc t = Sc t (z)…”
Section: Environmental Flow Commentsmentioning
confidence: 99%
“…Ross [71] performed numerical simulations of scalar transport in neutral flow over forested hills using both a 1.5-order mixing-length closure scheme and LES. He found that the common assumption that momentum and scalars are transported in the same way is not valid within and just above the canopies, with strong variations in Sc t in the vertical direction and across the hill.…”
Section: Environmental Flow Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…() found that gentle topography (sinusoidal ridges) led to significant spatial variability in fluxes of C O 2 at the canopy top when photosynthetic sinks and soil respiration sources are considered together. Two‐dimensional model runs reported by Ross () using a uniform gas source within the entire canopy volume confirms the existence of enhanced fluxes in the separation region. Their results also showed that the efficiency of gas transport out of the canopy is enhanced by topography, leading to lower in‐canopy concentrations when compared to flat terrain.…”
Section: Introductionmentioning
confidence: 97%
“…BLASIUS has previously been used for other studies of canopy flow, both as a one-and-a-half order mixing-length closure model (Ross and Vosper, 2005;Ross, 2011), and as a large-eddy simulation (LES) model (Ross, 2008(Ross, , 2011. Here the model is run with the one-and-a-half order mixing-length closure scheme.…”
Section: Long and Short Wavelength Variations In Canopy Densitymentioning
confidence: 99%